Meltwater Contribution to Lake Water Budget in Mid‐Latitude Asia During the Deglaciation and Early Holocene. Issue 22 (18th November 2022) - Jiang, Jiawei; Liu, Hu; Jiang, Qingfeng; Chang, Yuan‐Pin; Song, Mu; Meng, Bowen; Wang, Huanye; Cao, Yunning; Shen, Ji; Krivonogov, Sergey; Liu, Weiguo; Liu, Zhonghui
Abstract: Contrasting moisture evolutions between westerlies‐dominated Central Asia and monsoonal Asia since the mid‐Holocene have been widely recognized. Yet, inconsistent hydrological records over the early Holocene from both regions hamper our understanding of hydroclimatic changes and associated mechanisms. Here we present isotopic and biomarker (alkenone) records from three Chinese lakes located at both regions to address a possible meltwater role in lake water budget. Our results show the occurrence of particularly depleted isotopic values of lake water associated with lake freshening within the deglaciation and early Holocene. Together with anomalously old 14 C dates, which were also documented in many other Asian lakes, our observations likely indicate substantial meltwater contribution to mid‐latitude Asian lake water budget, along with the climatic warming. Hence, the potential meltwater effect should be considered when inferring Asian summer monsoon and westerlies behavior over this critical period, with important implications to Holocene hydrological reconstructions and future hydroclimatic projections. Plain Language Summary: Although meltwater events have been well documented in marine records, the effects of meltwater on Asian lake water budget and regional hydrological cycle during the deglaciation and warm early Holocene remain poorly investigated. Our isotopic and biomarker records from Lake Sayram, Yanhaizi, and Qinghai in northern China, together with anomalously old 14 C dates from investigated lakes and other Asian lakes, likely indicate substantial meltwater contribution to lake water budget within the deglaciation and early Holocene, which appears to be a large‐scale phenomenon in mid‐latitude Asia. This suggests that the potential meltwater effect on Asian lake hydrology should be assessed in climatic reconstructions and simulations, which may shed light on accurate interpretation of westerlies and summer monsoon circulation over the early Holocene. Key Points: Isotopic records likely indicate meltwater contribution to Asian lake water budget within the deglaciation and early Holocene Anomalously old 14 C dates summarized from mid‐latitude Asian lakes also support substantial meltwater input during this period Meltwater effects should be considered when inferring early Holocene Asian summer monsoon and westerlies behavior